Systemic and Nonrenal Adverse Effects Occurring in Renal Transplant Patients Treated with mTOR Inhibitors - Gianluigi Zaza; Paola Tomei; Paolo Ria; Simona Granata; Luigino Boschiero; Antonio Lupo (Clinical and Developmental Immunology)
The mammalian target of rapamycin inhibitors (mTOR-I), sirolimus and everolimus, are immunosuppressive drugs largely used in renal transplantation. The main mechanism of action of these drugs is the inhibition of the mammalian target of rapamycin (mTOR), a regulatory protein kinase involved in lymphocyte proliferation. Additionally, the inhibition of the crosstalk among mTORC1, mTORC2, and PI3K confers the antineoplastic activities of these drugs. Because of their specific pharmacological characteristics and their relative lack of nephrotoxicity, these inhibitors are valid option to calcineurine inhibitors (CNIs) for maintenance immunosuppression in renal transplant recipients with chronic allograft nephropathy. However, as other immunosuppressive drugs, mTOR-I may induce the development of several adverse effects that need to be early recognized and treated to avoid severe illness in renal transplant patients. In particular, mTOR-I may induce systemic nonnephrological side effects including pulmonary toxicity, hematological disorders, dysmetabolism, lymphedema, stomatitis, cutaneous adverse effects, and fertility/gonadic toxicity. Although most of the adverse effects are dose related, it is extremely important for clinicians to early recognize them in order to reduce dosage or discontinue mTOR-I treatment avoiding the onset and development of severe clinical complications.